REFLECTIONS ON THE INTERVIEW AS A HISTORICAL DOCUMENT AND ARCHIVE MATERIAL - Dusaillant, Jacqueline (Revista de Historia Social y de las Mentalidades, 2024)
The interview has been used to gather information by researchers from different disciplines and using different methods and technologies. This article reviews the main problems associated with the interview in the context of the emergence of oral history, both from the perspective of its creation and conservation, and its use when it is integrated into a public access Archive. It concludes that if at the beginning the main challenges for archivists and historians lay in the methodology and relevance of the interview as a means and product, in the last decades they have concentrated on ethical and legal aspects.
Keywords: Interview; Oral History; Archive; Intellectual Property